2014
DOI: 10.1039/c4cp02788d
|View full text |Cite|
|
Sign up to set email alerts
|

High throughput first-principles calculations of bixbyite oxides for TCO applications

Abstract: We present a high-throughput computing scheme based on density functional theory (DFT) to generate a class of oxides and screen them with the aim of identifying those that might be electronically appropriate for transparent conducting oxide (TCO) applications. The screening criteria used are a minimum band gap to ensure sufficient transparency, a band edge alignment consistent with easy n- or p-type dopability, and a minimum thermodynamic phase stability to be experimentally synthesizable. Following this schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 64 publications
3
21
0
Order By: Relevance
“…The origin of this difference may be the incomplete counteraction of self‐interaction induced by the localized hole states, as mentioned in previous work . Advanced methods, such as GW [13,14] or hybrid functionals based on fixed experimental lattice constants, substantially improve band structure calculations and reproduce the variation behavior found by Prokofiev et al, as reported in our previous work and that of Jiang et al Additionally, our previous work found that the use of such methods as hybrid functionals in conjunction with pseudopotential methods can also introduce errors in the DFT‐predicted lattice parameters and defect levels …”
Section: Introductionmentioning
confidence: 54%
“…The origin of this difference may be the incomplete counteraction of self‐interaction induced by the localized hole states, as mentioned in previous work . Advanced methods, such as GW [13,14] or hybrid functionals based on fixed experimental lattice constants, substantially improve band structure calculations and reproduce the variation behavior found by Prokofiev et al, as reported in our previous work and that of Jiang et al Additionally, our previous work found that the use of such methods as hybrid functionals in conjunction with pseudopotential methods can also introduce errors in the DFT‐predicted lattice parameters and defect levels …”
Section: Introductionmentioning
confidence: 54%
“…In particular, high-throughput first-principles calculations based on density functional theory (DFT) [12,13] are powerful when generating large data for both known and hypothetical materials [14][15][16][17][18]. With the aid of methods for high-throughput computations [17,[19][20][21][22][23][24][25], such data have been used in many studies for understanding the tendency of physical and chemical properties and exploring novel materials [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], some of which effectively combine machine learning techniques [33][34][35][36]. High-throughput first-principles calculations have also been used for studying metal oxide systems, for instance to explore transparent conducting oxides [37,38], photocatalysts [39][40][41], and high-κ dielectrics [42].…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput ab initio computations, on the other hand, can be used to screen large classes of materials, searching for those that exhibit a predetermined basic set of properties, qualifying them as potential candidates for a specific application 19 20 . This approach has already been used in the search for novel organic p -type semiconductors (not transparent) 21 and candidate TCO materials 16 22 , as well as new thermoelectric 23 , piezoelectric 24 and scintillator materials 25 .…”
mentioning
confidence: 99%